Warm homes for older people: aims and methods of a randomised community-based trial for people with COPD - Viggers, Helen (BioMed Central, 2013)
BACKGROUND: Chronic Obstructive Pulmonary Disease (COPD) is of increasing importance with about one in four people estimated to be diagnosed with COPD during their lifetime. None of the existing medications for COPD has been shown to have much effect on the long-term decline in lung function and there have been few recent pharmacotherapeutic advances. Identifying preventive interventions that can reduce the frequency and severity of exacerbations could have important public health benefits. The Warm Homes for Elder New Zealanders study is a community-based trial, designed to test whether a NZ$500 electricity voucher paid into the electricity account of older people with COPD, with the expressed aim of enabling them to keep their homes warm, results in reduced exacerbations and hospitalisation rates. It will also examine whether these subsidies are cost-beneficial. METHODS: Participants had a clinician diagnosis of COPD and had either been hospitalised or taken steroids or antibiotics for COPD in the previous three years; their median age was 71 years. Participants were recruited from three communities between 2009 to early 2011. Where possible, participants’ houses were retrofitted with insulation. After baseline data were received, participants were randomised to either ‘early’ or ‘late’ intervention groups. The intervention was a voucher of $500 directly credited to the participants’ electricity company account. Early group participants received the voucher the first winter they were enrolled in the study, late participants during the second winter. Objective measures included spirometry and indoor temperatures and subjective measures included questions about participant health and wellbeing, heating, medication and visits to health professionals. Objective health care usage data included hospitalisation and primary care visits. Assessments of electricity use were obtained through electricity companies using unique customer numbers. DISCUSSION: This community trial has successfully enrolled 522 older people with COPD. Baseline data showed that, despite having a chronic respiratory illness, participants are frequently cold in their houses and economise on heating. TRIAL REGISTRATION: The clinical trial registration is http://NCT01627418